Methods to Overcome the Barriers and The Disintegration Effect of Port Areas in The City Center and The Factors Determining Their Choice - Tanov , Mladen (ICONARCH International Congress of Architecture and Planning, 2014)
Port warehouse complexes and transport infrastructure around them, located near the urban centers of major cities are huge barriers and buffers in urban organism. Once engines for the emergence and development of cities, in the last 40 years these areas act as restraints in the development of cities. At the same time historically formed cities also do not allow modernisation and expansion of ports. Economic dynamics and the new functional profile of the coastal towns exert asignificant pressure for change, requiring the transformation of these large areas for new features, their opening to wider user groups and their greater commitment to the historic core of the town. What are the opportunities to reconnect the city to the coast, to extend the city center and accommodate new needs, increase pedestrian, recreational and green areas near the center and improve the overall quality of living environment? In some cases this is achieved through the transformation of part of the port complexes in open public areas, enriched by various social-service and recreational activities. In others - through the complete removal or relocation of activities (port, warehouse, industrial) and a new design/redesign of the towns. In the yet other - through purely spatial-invasive solutions that give people access to water without changing port areas. The report examines the factors determining the regeneration solution and the main methods of approach based on analysis of 12 realized coastal transformations and several approved but unrealized projects. Particular attention is paid to the functional profile of the renovated areas and predominant functions in the mix and the inclusion of these new parts in the functioning of the urban organism.